Community based adaptation and resilience in East and Southern African drylands - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
1-4 September 2014 saw the coming together of 80 participants from 11 countries to discuss the future of drylands in East and Southern Africa through community based adaptation. The participants discussed the various opportunities that can improve the drylands. Photos: S.Kilungu (CCAFS)